Participatory evaluation of tomato (Lycopersicon esculentum Mill.) varieties under irrigation conditions at Abergelle district, Eastern Amhara - Mihiretu, A.; Asresu, M. (International Journal of Horticultural Science, 2023)
Participatory on-farm evaluation of improved tomato varieties (‘Melka salsa’, 'Roma VF' and 'Kochero’) against the local tomato variety was carried out during the 2019/2020 growing season involving six farmers of Abergelle district, Eastern Amhara. The objective of the experiment was to assess the performance of different tomato varieties for the farmers, then to collect their feedback. Based on the actual and farmers’ preference data, the analysis underscores the better performance of improved tomato varieties over local varieties by most yield-related attributes. Average marketable fruit yields of ‘Melka salsa’, ‘Roma VF’, ‘Kochero’, and the local variety were 4.62, 3.88, 3.64, and 3.10 ton ha-1, respectively. The improved varieties thus had a yield advantage of 72.38%, 37.14%, and 25.72% over the local variety in that order. Among improved tomato varieties, ‘Melka salsa' provided the highest fruit yield on top of owing the highest score of overall preference attributes rank. Scale-wide diffusion of ‘Melka salsa’ tomato variety is therefore suggested for similar and potential agro-ecologies. Biological scientists also should take farmers’ preference attributes and feedback as a backup for future breeding and adaptation studies on tomato varieties.